PROBLEMS OF PREPARING PRE-SERVICE INFORMATICS TEACHERS TO FORM STUDENTS' INFORMATION-INTELLECTUAL COMPETENCIES - Кhalikova, К.З.; Seisenbekova, П.Б (Bulletin of Abai KazNPU. Series of Physical and Mathematical sciences, 2024)
The problems of training pre-service Informatics teachers to develop the information and intellectual competence of students are considered in this article. The analysis results of studies related to the formation of information and intellectual competence in the investigations of domestic and foreign researchers are presented. The development components of information and intellectual competence of students have been identified, a model for the development of information and intellectual competence of pre-service Informatics teachers has been created, and on the basis of this model a training program has been developed in the subject “Artificial Intelligence Technologies”. The effectiveness of the proposed training program for this subject was tested experimentally, and statistical methods (Student's t-test) were used to process its results. The results obtained are theoretical in nature and the model for the development of information and intellectual competence of pre-service Informatics teachers obtained on the basis of the proposed curriculum can be used when teaching the subject “Artificial Intelligence Technologies”. This model contributes to the development of information and intellectual competencies of pre-service Informatics teachers through the use of innovative teaching methods.